Postural control in elite archers during shooting - Lin, W. H.; Huang, G. T.; Chiu, P. K.; Lee, A. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Archery is described as a static sport requiring fine movement control and proper endurance strength of the upper body (Soylu, Ertan, & Korkusuz, 2006).To investigate the differences of postural control (PC) between elite and general collegiate archers during static and shooting conditions.